First swim record of Herpailurus yagouaroundi in Guatemala - Escobar-Anleu, Bárbara; Quiñónez-Guzmán, Juan; Hernández-Gómez, Sergio (Therya Notes, 2020)
The jaguarundi (Herpailurus yagouaroundi) is a species of neotropical felid with diverse eating habits and it is present in different types of habitat. On February 6, 2018, we observed and recorded an individual of this species swimming in an area with seagrass, in Bahia la Graciosa, in the Punta de Manabique Wildlife Refuge, Izabal, Guatemala. In this note, we report the first record of swimming behavior for this species, which we believe can be attributed to the individual searching for food in the area. Although the jaguarundi is considered a generalist species, knowledge about its behavior and populations, in general, is scarce. This is why we consider this first report to be a valuable contribution to the knowledge of this neotropical felid. Appendix